Социальная аномия как криминологический феномен - Дрьомін, В. Н.; Дремин, В. Н.; Dryomin, V. (My University, 2011)
The article deals with social anomie as a criminological phenomenon. The problem of anomie becomes particularly signiﬁ cant in "transitive" societies, which are known for their feature of economic and political systems' transformation. The extension of anomie is a consequence of the loss of spiritual values and a wide spread of legal nihilism within the population. By its behavioral impact the social anomie is being one of the major criminogenic factors. The suppression of antisocial collective values' outspread should be the leading trend in combating crime.
Социальная аномия как криминологический феномен
Дрёмин В. Н. Социальная аномия как криминологический феномен / В. Н. Дрёмин // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. – Одеса : Фенікс, 2011. – Вип. 42. – С. 230 - 240.
Keywords: соціальна аномія; кримінологічний феномен; соціальні норми; асоціальні колективні цінності; социальная аномия; асоциальные коллективные ценности; социальные нормы; криминологический феномен; criminological phenomenon; social norms; asocial collective values; social anomie